Re-framing HCI through Local and Indigenous Perspectives - Jose, Abdelnour-Nocera; Masaaki, Kurosu; Torkil, Clemmensen; Nic, Bidwell; Ravi, Vatrapu; Heike, Winschiers-Theophilus; Vanessa, Evers; Rüdiger, Heimgärtner; Wee, Alvin Yeo (Springer Berlin Heidelberg, 2011)
This one-day workshop aims to present different local and indigenous perspectives from all over the world in order to lead into an international dialogue on re-framing concepts and models in HCI/Interaction Design. The target audience is HCI researchers and practitioners who have experience with working with culture and HCI. The expected outcome of the workshop is a) network building among the participants, b) a shortlist of papers that can be basis for a proposal for a special issue of the UAIS journal, and c) identify opportunities to develop a funded network or research proposal.